Changing Norms is Key to Fighting Everyday Corruption - Panth, Sabina (World Bank, Washington, DC, 2014)
One of the biggest impediments to anticorruption efforts is the fact that corrupt practices have become so institutionalized in everyday society that citizens view them as fixed and incontestable. To break down such an entrenched mind-set, the public s ignorance of their rights, cynicism, fear of reprisal, and mentality of submission to the status quo must first be defeated. Perhaps most important, the efficacy challenge needs to be addressed. Citizens generally must believe that they can actually do something about corruption in order to summon the courage to act upon that belief. Based on CommGAP s interactions with the global anticorruption community as well as earlier research, we were able to collate 18 representative instances (case studies) from around the world, with real-life examples of citizens coming together to speak up against corruption and social norms vis-à-vis corruption or to change public services affected by corrupt practices. This report is a one-step-up analysis of the collated case studies, which is intended to shed light on practical approaches, tools, and techniques that have been successful in bringing citizens together to stand against the daunting phenomenon of corruption.